ISOLASI Campylobacter DARI KARKAS AYAM MENGGUNAKAN METODE KONVENSIONAL DAN POLYMERASE CHAIN REACTIONS [Isolation of Campylobacter from Poultry Carcasses using Conventional and Polymerase Chain Reaction Methods] - . Andriani; Mirnawati Sudarwanto; Surachmi Setiyaningsih; Harsi Dewantari Kusumaningrum (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
ABSTRACT Campylobacter jejuni and Campylobacter coli are two spesies of Campylobacter sp. frequently found as pathogenic bacteria causing human gastrointestinal infections. Contaminated chicken carcasses have been reported as the source of human campylobacteriosis. In this study, Campylobacter were isolated from chicken carcasses sold in traditional markets and supermarkets. In traditional markets, chicken carcasses are sold without proper packaging or in an open space and stored at room temperature (25-30°C) for prolonged period allowing pathogenic bacteria to grow. While at supermarkets, chicken carcasses are openly displayed or enclosed in plastic wrappings and stored in a refrigerator (4-8°C). A total of 298 samples of chicken carcasses from traditional markets and supermarkets in the area of DKI Jakarta, West Java (Bogor and Sukabumi) and Central Java (Kudus and Demak) were collected. Isolation and identification using conventional and Polymerase Chain Reactions (PCR) methods were done to determine the prevalence of C. jejuni and C. coli contamination in poultry. The results showed that chicken carcasses sold in the sampling area, both traditional markets and supermarkets, were contaminated with C. jejuni and C. coli. The contamination rate of Campylobacter sp. in chicken carcasses sold in supermarkets, were 14.1% by conventional methods and 29.5% by PCR. This was higher than those in traditional markets, i.e. 5.7 and 12.1%, respectively. It is also confirmed that the prevalence for contamination of C. jejuni was higher than C. coli in 298 samples, i.e. 16.1% and 3.7% by conventional method and 23.5% and 18.1% by PCR method respectively. Keywords: Campylobacter coli, Campylobacter jejuni, poultry carcasses, supermarket, traditional market